QUALITY ASSURANCE SYSTEM BETWEEN THE ISLAMIC STATE UNIVERSITY AND THE STATE UNIVERSITY - Fitri, Agus Zainul (Jurnal Pendidikan Islam, 2016)
The purpose of this research is to compare the quality assurance system in the Islamic State University at Universitas Islam Negeri (UIN) of Malang and The State University at Technical Institute of Surabaya (Institut Teknik Surabaya/ITS).Â The findings concerning quality assurance system cover; the reasons for implementing the quality assurance, the core value of quality planning, the quality assurance of implementation, the quality assurance of evaluation, the supporting factor of the implementation of quality assurance, the quality assurance strategy, and the result of quality assurance. This study uses exploratory mixed method research design with the developmental model instrument. While the process of this research starts with collecting qualitative data, then the extreme finding is followed by collecting quantitative data, and the end of this process is interpreting data together. From the qualitative data, it can be concluded that there is a difference between quality assurance in UIN Malang and ITS. The quality assurance in the institution management (X), the academic aspect (Y), and customersâ€™ satisfaction (Z) was significantly different (significantly) between UIN Malang and ITS.Â Customersâ€™ satisfaction at UIN Malang is influenced by the quality of management and academic with a larger proportion than in ITS.